Advancing knowledge about lifelong crime sequences - Pereira, Miguel Basto (The British journal of criminology, 2019)
This article aims to describe the most prevalent, lifelong sequences of crime, to identify developmental patterns of crime, and to evaluate the impact of childhood characteristics on each pathway. Convictions up to age 56 in the Cambridge Study in Delinquent Development are analyzed. The prevalence of the most frequent sequences of convictions is presented. Optimal matching dissimilarity and partitioning around medoids analyses are conducted to identify types of sequences. The most common sequences of convictions involve types of stealing. Four different types of sequences are identified and are predicted using childhood characteristics. It is concluded that different types of childhood vulnerabilities predict different types of conviction sequences.